Pengujian Unsur Penyalahgunaan Terkait Tindak Pidana Korupsi di PTUN dan Kewenangannya - Malik Muhammad Mad; Arif Wibowo; Sumardi Efendi (SHIBGHAH: Journal of Muslim Societies, 2023)
The objective to be achieved in this study is to Review, know andanalyze the logical ratio of Article 21 paragraph (1) of Law No. 30 of 2014 on Government Administration, which authorizes the State Administrative judiciary to test the elements of abuse of authority and implications of ptun authority in testing abuse of authority against the enforcement of corruption crimes. The method used in this study is Normative legal research with legal material tracing techniques conducted with Pustaka studies. The results of the research with the above method show that the logical ratio of Article 21of Law No. 30 of 2014 on Government Administration is Supervision by the State Administrative Court as a means of preventing abuse of authority in decisions and /or actions (discretion) by government administration officials carrying out service duties and legal implications that can arise from the authority of the State Administrative Court to test whether or not abuse of authority related to corruption crimes is that the Authority of state administrative judiciary carries implications in the enforcement process of corruption crimes.